2019
DOI: 10.4269/ajtmh.18-0906
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance May Be More Appropriate Than Immunity When Describing Chronic Malaria Infections

Abstract: Adults who have not grown up in a malaria-endemic area may experience severe malaria soon after entering a malarious area. Such mortality is usually limited to a short period of time (months), after which they are thought to be "immune." Such anti-disease immunity may be more accurately considered as tolerance. Malaria rates of British soldiers during the Second World War reflected their time with suppressed infections and the transmission levels. Black workers from non-endemic areas on the Panama Canal experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This immune tolerance is also supported by the rst series of experimental malaria infections in humans, which revealed that the risk of fever decreases with the number of infections [49]. According to Shanks [50], parasites in asymptomatic carriage bene t from relative immune tolerance and adults exercise better control over parasite density and genotypic uctuations. Indeed, antibodies can be classi ed into two groups, those acquired during early childhood, resulting from the primary infection, short-lived in nature, considered as marker of exposure and those with a long lifespan acquired through repeated infections and associated with protection [51,52,53].…”
Section: Discussionmentioning
confidence: 88%
“…This immune tolerance is also supported by the rst series of experimental malaria infections in humans, which revealed that the risk of fever decreases with the number of infections [49]. According to Shanks [50], parasites in asymptomatic carriage bene t from relative immune tolerance and adults exercise better control over parasite density and genotypic uctuations. Indeed, antibodies can be classi ed into two groups, those acquired during early childhood, resulting from the primary infection, short-lived in nature, considered as marker of exposure and those with a long lifespan acquired through repeated infections and associated with protection [51,52,53].…”
Section: Discussionmentioning
confidence: 88%
“…Chronic and subclinical as well as low-parasitemic Plasmodium infections do not induce strong inflammatory responses in endemic settings ( 8 , 25 ). Upon repeat exposure to the parasite, anti-disease immunity develops first, followed by anti-parasitic immunity that can be highly effective ( 26 28 ) – up to sterile immunity in a small percentage of individuals ( 29 , 30 ). In contrast to sterile immunity, anti-disease immunity is characterized by developing tolerance to parasitemia ( 31 ), which can be associated with a more general immunosuppression ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity to restrict the infection burden and control inflammation and immune activation are major determinants of the malaria clinical outcomes (reviewed in [9, 10]). The ability to control parasite load results from anti-microbial immune responses and leads to pathogen elimination and resistance to infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…The capacity to restrict the infection burden and control inflammation and immune activation are major determinants of the malaria clinical outcomes (reviewed in [9,10]).…”
Section: Introductionmentioning
confidence: 99%